Evaluating the performance of Kuwait International Bank "An analytical study of the effects of the convert from the conventional system to the Islamic system " (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This research aimed to recognize the extent of reflecting the application of Islamic banking system on the financial performance of banks. It's also helps to find the feasibility sought by the conventional banks by directing to converting to the Islamic system through evaluating the financial performance of the conventional banks before and after its shift; by using the financial indicators and the personal interviews that answered the main question of the research which is;  Is there a difference in the bank's performance before and after the shift from the conventional system to Islamic system? The most important research results were that the pre-preparation of the bank shift plan and the creation of its employees is one of the most important factors in the success of the process. Also the possibility of banks converting in the state of Kuwait is available and enacted with laws that regulate working therein. The financial ratios are also main indicators to identify the performance of the bank. The professional vision of the bank converting experience has also suggested the right decision to turn to the Islamic regime to achieve the desired end of all the technical aspects, including banking, financial and legal ones.